Synthesis of FexZn1-xCr2O4 brown ceramic pigment by starch-assisted sol-gel process - Tuyen, Tran Ngo; Quyen, Nguyen Duc Vu; Lam, Tran Bao (Hue University Journal of Science: Natural Science, 2019)
In the present paper, the ceramic pigments FexZn1-xCr2O4 (x = 0 ¸ 1) were synthesized with the starch-assisted sol-gel method. The resulting pigments were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and CIE L*a*b* color measurement. The results show that FexZn1-xCr2O4 pigments form at sintering temperature of 1100 OC for 60 minutes. The ACr2O4 spinel (A: Zn, Fe) and FeCrO3 perovskite phase with excellent crystallinity appears. The brown color intensity increases gradually with the increase of the number of substituted Fe2+ cations. The pigments meet industrial requirements in terms of physicochemical characteristics.